Penerapan Pembelajaran E-Learning terhadap Minat Belajar Siswa Selama Pandemi Covid-19 - Mohzana, Mohzana (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the effect of implementing e-learning on the learning interests of Madrasah Aliyah students in East Lombok during the Covid -19 pandemic. The type of research used is causal associative quantitative research. The subjects of this research were Madrasah Aliyah students in East Lombok with 71 respondents. The population in this study were all students of Madrasah Aliyah in East Lombok with a proportionate stratified random sampling technique, taking 20% of the total population. Data collection techniques using a questionnaire (questionnaire). Data analysis technique using linear regression. The results of the study show that online learning variables have a significant effect on learning interest with tcount > ttable (5.230 > 1.994). So it is concluded that the application of online learning through e-learning can increase student interest in learning and provide alternative effective learning methods for education in the future. Keywords: Covid-19, E-learning, interest in learning, online learning